2021
DOI: 10.1080/10717544.2021.1902023
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-based nano-formulation platform for eplerenone oral delivery as a potential treatment of chronic central serous chorioretinopathy: in-vitro optimization and ex-vivo assessment

Abstract: Purpose Eplerenone (EPL) is a selective mineralocorticoid receptor antagonist used for treatment of chronic central serous chorioretinopathy which characterized by accumulation of subretinal fluid causing a localized area of retinal detachment. unfortunately, EPL suffers from poor oral bioavailability due to poor aqueous solubility in addition to high hepatic first pass metabolism. Method Aiming to improve its oral bioavailability, EPL-loaded nanostructured lipid carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…This difference in hydrophobicity allows their orientation to form micelles in the aqueous phase ( Thapa et al, 2020 ). Thus forming a rigid layer of surfactant around the formed particles, preventing drug leaking and offering better drug housing and so better drug EE% ( Abdelhakeem et al, 2021 ). These results came in agreement with the results found by Zafar et al ( Zafar et al, 2022 ) who prepared NLCs-based erythromycin gel and revealed that the increase of Pluronic F127 (poloxamer 407) from 2% to 5% was accompanied by an increase in EE %.…”
Section: Resultsmentioning
confidence: 99%
“…This difference in hydrophobicity allows their orientation to form micelles in the aqueous phase ( Thapa et al, 2020 ). Thus forming a rigid layer of surfactant around the formed particles, preventing drug leaking and offering better drug housing and so better drug EE% ( Abdelhakeem et al, 2021 ). These results came in agreement with the results found by Zafar et al ( Zafar et al, 2022 ) who prepared NLCs-based erythromycin gel and revealed that the increase of Pluronic F127 (poloxamer 407) from 2% to 5% was accompanied by an increase in EE %.…”
Section: Resultsmentioning
confidence: 99%
“…They are also reported for high drug load without drug leakage [ 5 ], which enhances drug release and bioavailability [ 11 ]. Various studies published on ocular NLCs report a high corneal contact time in comparison to pure drug solution [ 5 , 12 , 13 , 14 ]. They report a significant enhancement in corneal permeation and a decrease in ocular clearance.…”
Section: Introductionmentioning
confidence: 99%
“…These encapsulated bioactive compounds reflected slower release due to slower erosion of lipid wall matrix (12 h). Another study conducted by Abd-Elhakeem et al [139] illustrated about improving the bioavailability and oral target delivery of eplerenone by using lipid-based nanoencapsulation. Eplerenone-loaded nano-lipid capsules reflected in improved permeability up to two folds higher compared to conventional aqueous drug in rabbit intestine after the period of 24 h.…”
Section: Lipid-based Nano-carriersmentioning
confidence: 99%